Towards international comparative research on the professionalisation of Religious Education - Freathy, Rob (Journal of beliefs and values, 2014)
This article calls for international comparative research on the professionalisation of Religious Education (RE). To this end, it provides a rationale for focusing upon the concept of professionalisation and a theoretical justification for international comparative research, particularly identifying its significance in terms of the development of RE in England and Germany. The article outlines a methodology for exploring the concepts of professional knowledge, professional self-organisation and politics and professional development. The proposed methodology involves a systematic analysis of primary documentary sources including: (1) academic and professional journal articles and textbooks; (2) the archives of relevant institutions and organisations; and (3) external evidence, such as inspection and research reports. An analytical case study of two leading journals in each national context, Religion in Education in England and Der Evangelische Erzieher in Germany, in the immediate post-war era is appended to illustrate the benefits of implementing such a methodology across national boundaries.